Fault location using mathematical analysis and database approach. Issue 1 (28th November 2018) - Gururajapathy, Sophi Shilpa; Mokhlis, Hazlie; Illias, Hazlee Azil
Abstract : Purpose: The purpose of this paper is to identify faults in distribution systems which are unavoidable because of adverse weather conditions and unexpected accidents. Hence, quick fault location is vital for continuous power supply. However, most fault location methods depend on the stored database for locating fault. The database is created by simulation, which is time consuming. Therefore, in this work, a comprehensive fault location method to detect faulty section and fault distance from one-ended bus using limited simulated data is proposed. Design/methodology/approach: The work uses voltage sag data measured at a primary substation. Support vector machine estimates the data which are not simulated. The possible faulty section is determined using matching approach and fault distance using mathematical analysis. Findings: This work proposed a ranking analysis for multiple possible faulty sections, and the fault distance is calculated using Euclidean distance approach. Practical implications: The research work uses Malaysian distribution system as it represents a practical distribution system with multiple branches and limited measurement at primary substation. The work requires only metering devices to identify fault which is cost effective. In addition, the distribution system is simulated using real-time PSCAD by which the capability of proposed method can be fully tested. Originality/value: The paper presents a new method for fault analysis. It reduces simulation time and storage space of database. The work identifies faulty section and ranks the prior faulty section. It also identifies fault distance using a mathematical approach.